Level of Knowledge, Attitude and Practice of Doping among Ethiopian Professional Middle and Long Distance Runners - Desalegn(Ph.D), Mesay; Haile , Temesgen; Andargachew, Yohannes; Endris, Mohammed; Agegnehu, Daniel; Walle, Ali; Abubeker, Osman; Getahun, Yeshwas (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2020)
Introduction: - Doping, defined as use of drugs or other substances for performance enhancement, has become an important topic in virtually every sport and has been discovered in athletes of all ages and at every level of competition. The efficient strategy for prevention of doping use throughout the sport calendar requires improving the level of knowledge and hastening the development of negative attitude and practice towards doping in the athletes society. Objectives: - The aim of the study was to determine the level of knowledge, attitude and practice on doping among Ethiopian professional middle and long distance runners,2016/17, Ethiopia. Methods: - A quantitative cross-sectional study design was conducted in Ethiopia from December 15, 2016 to January 14, 2017. The study included 775 Ethiopian middle and long distance running athletes. The study participants were selected by using multi stage sampling technique. Data were collected using structured and pretested questionnaires and multivariate logistic regression analyses were done to identify factors associated with knowledge and attitude towards doping. Finally, results were presented with appropriate tables and graph as well as adjusted odd ratio (AOR) and 95% confidence interval. Results: - The prevalence of adequate knowledge, unfavorable attitude and self-reported practice of doping were 18.5%, 70.8% and 3.6% respectively. Educational status of college and above, married and attending of anti-doping training were found to be significantly associated with knowledge of doping. In terms of attitude age, educational status, residence, attending training on anti-doping and parental factors were showed statistically significant association. Conclusion: - The prevalence of adequate knowledge of doping was quite low and unfavorable attitude towards doping was moderate. In regarding to practice of doping a significant number of athletes were reporting they were using it. Adequate knowledge of doping was higher among athletes who had higher educational status, were married, and attending training on anti-doping.